Determination of a rational structure of the security service integrated logistical support system based on regional logistics clusters - Sysoiev, Volodymyr Viktorovych (Institute of Technology and Business in Ceske Budejovice, 2013)
Development of an integrated logistical support system for all types of national security services requires the solution to a problem of definition its rational structure. The methodical approach proposes to consider this issue as a complex of two successive optimization tasks. In the first place, it assumes to determine regional logistics clusters amount and then to optimize their logistics infrastructure. The models and methods are developed to allow optimization of the integrated logistical support system structure according to a real transport network communications and a regional supply chain by a minimal total logistics costs criterion.
Stanovení racionální struktury bezpeýnostní služby integrovaného logistického podporného systému založeného na regionálních logistikých klastrech
Keywords: rational structure; Security Service integrated logistical support system; regional logistics clusters; total logistics costs; optimization